Gender Differences in Peripheral Vascular Disease - Schramm, Kristofer; Rochon, Paul J. (Seminars in Interventional Radiology, 2018)
In the past 20 years, peripheral artery disease (PAD) has been increasingly recognized as a significant cause of morbidity and mortality in the United States. PAD has traditionally been identified as a male-dominant disease; however, recent population trends and studies in PAD suggest that women are affected at least as often as men. Women comprise a larger population of the elderly than men, as well as an increasing proportion of patients with PAD. Much of the existing research on PAD has focused on whole populations, and gender-specific data on PAD is sparse. This review focuses on gender-specific differences in presentation, management, and outcomes of PAD intervention that are important considerations for the interventional radiologist.
Keywords: interventional radiology; peripheral arterial disease; gender; medical therapy